If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5=-2p+3p
We move all terms to the left:
5-(-2p+3p)=0
We add all the numbers together, and all the variables
-(+p)+5=0
We get rid of parentheses
-p+5=0
We add all the numbers together, and all the variables
-1p+5=0
We move all terms containing p to the left, all other terms to the right
-p=-5
p=-5/-1
p=+5
| y/4+11=13 | | 6t+11=89 | | 14-2w=10 | | 8=m/2 | | 3(c+80)=24 | | (4x+1)/2=x+7 | | 6x-6=22+2.5x | | u+2.28=6.61 | | 3(x+1)=2(x+3)1 | | f-27=32 | | 100=20c | | 6(c+1)=66 | | p/3+10=14 | | y-54=68 | | 15=2y-25 | | 5x/18-4x/15=90 | | 5u(u-7)(u-6)=0 | | 0.5(x+2)+2=0.75(x-20) | | 6x-1=2(x+5) | | 1467+x=1653 | | s-18/8=6 | | 6=-2+u/2 | | 7(d+2)=35 | | 5=2b+1 | | 4x+21-x^2=0 | | 5=v/9+1 | | -2(-x+8)=5(x+3) | | 4(x+3)=26-3x | | 50=x- | | 8(z-88)=24 | | 12x+5x=160 | | s/10-1=1 |